EFFECTS OF BRACHYTHERAPY ON QUALITY OF LIFE AND FUNCTIONALITY IN THE TREATMENT OF CERVIX CANCER - Corpes, Erilaine de Freitas; Gonçalves, Gerciane dos Anjos; Oliveira, Ana Caroline Andrade; Pacífico, Viviane da Silva; Castro, Régia Christina Moura Barbosa; de Almeida, Paulo César; Barbosa, Isadora Marques (Cogitare Enfermagem, 2022)
Objective: to assess the effect of brachytherapy on functionality and quality of life of women with cervix cancer. Method: a descriptive and cross-sectional study carried out between December 2019 and February 2020 with 33 women with uterine neoplasia undergoing brachytherapy, followed up at Centro Oncológico do Nordeste - Brazil. The Funtional Assessment of Cancer Therapy – Cervix Cancer instrument was applied. The means of the subscales were compared and their mutual correlation was analyzed by applying the ANOVA and Student’s t tests. Results: requirements focused on self-image, sexuality and urinary complaints were evidenced. The mean of additional concerns was lower in the age group from 50 to 59 years old, when compared to the mean values in the age groups from31 to 49 years old (p=0.004) and from 60 to 75 years old (p=0.002). Conclusion: addressing issues related to sexuality and urinary complaints contribute to early identification of the symptoms caused by brachytherapy, as well as the implementation of measures, providing quality of life for the patient.